Dynamic Volatility in Stock Market Returns: An Evidence from Islamic Index and Kse100 Index of Pakistan - Rehman, Atta Ur; Nabi, Ghulam; Ullah, Hamid; Zeb, Naveeda; Khan, Muhammad Kamran; Ahmed, Masood; khan, Azhar (The journal of contemporary issues in business and government, 2021)
This paper examines the time-varying volatility in the stock returns at Pakistan Stock Exchange (PSX). Time series data was used to gauge the volatility in the stock returns trough time series analysis techniques including the ADF, ARCH and GARCH family modeling for this purpose. The volatility concept is much familiar in the stock market analysis especially in the future decision making process by the investor. To further investigate this phenomenon, an Islamic index and KSE100 index at PSX were chosen with daily data ranging from June, 2009 to august 2020 with the total daily observations of 2772. The data was collected from investing.com. The ADF and Phillips-Perron (PP) unit root tests were performed to check the stationary of the series, where it was confirmed that the stock return of the KMI30 index as well as KSE100 index were no unit root at 1(0). The ARCH LM lest confirmed the ARCH effects in the KMI30 and kSE100 indices. The GARCH family modeling including GARCH (1,1), Mean GARCH (1,1), EGARCH (1,1), and TGARCH (1,1) were used. The results revealed that stock returns of the Islamic index (KMI30) and KSE100 index at Pakistan Stock Exchange (PSX) have the feature of volatility clustering. It is also gauged that stock returns of KMI30 index and kSE100 index are more volatile to bad news than good news. The study further explored that holders of such stocks can diversify their investment in some other related stocks to get arbitrage opportunity.